Une fiction à la mesure du réel - Michaël Meyer; Héloïse Schibler (Communication)
The celebrated TV series The Wire has won praise from many media, political and social commentators. The authors analyze written material from the press and the Internet in order to understand how a “realism” discourse pertaining to the series was developed and disseminated. This discourse set up the series’ reference to “reality” as a benchmark for quality. Also present within the commentaries was a process for transforming fiction into reality.